Optimalisasi Metode Eklektik dalam Pengajaran Bahasa Arab di Lembaga Kursus Bahasa Arab Al-Fitrah Pare - Imroatul Ngarifah; Amrin; Laily Fitriani (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2022)
A method is important for a directed, effective, and efficient teaching process. One method in teaching Arabic is the eclectic method. This study aims to describe (1) the purpose and the planning of teaching Arabic and at Al-Fitrah Arabic Course Pare, (2) the implementation of eclectic methods in teaching Arabic at Al-Fitrah Arabic Course Pare, and (3) the optimalization of eclectic methods in teaching Arabic at Al-Fitrah Arabic Course Pare. This research is qualitative. Sources of data in this study are reports of interviews and observations. This study uses Miles and Huberman's data analysis technique which consists of data collection, data reduction, data display, and conclusion drawing. The results of this study show that (1) the purpose of teaching Arabic at Al-Fitrah Arabic Course Pare is that students could speak Arabic well, and the students classified into five levels, (2) Al-Fitrah Arabic Course Pare combines the direct method and the translate method, (3) optimalization the advantages of these two methods push teaching is more meaningful to achieve teaching purposes according to the plan.